Evaluasi penerapan PSAK No. 23 tentang pendapatan di Iloly Optical Manado - Paut, Marlina Elisabet; Pusung, Rudy Johanis; Latjandu, Lady Diana (Yayasan Widyantara Nawasena Raharja, 2025)
PSAK No. 23 is a Financial Accounting Standards Statement (PSAK) that regulates the recognition and measurement of revenue in financial statements. This study aims to analyze how the application of PSAK No. 23 on revenue in Iloly Optical Manado. The research method used is descriptive qualitative with interview, observation, and documentation techniques. The results of the study indicate that Iloly Optical Manado has carried out in accordance with PSAK No. 23. However, the disclosure of financial statement presentation is not in accordance with PSAK No. 23. The company's revenue recognition method uses an accrual basis, revenue is measured at fair value.